Artificial Intelligence in Inclusive Education: A Systematic Review of Teacher Competencies - Ade Putra; Achadi Budi Santosa; Enung Hasanah (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2026)
This study aims to systematically review the competencies required of teachers to implement AI in the context of inclusive education. A systematic review approach was used, referring to the PRISMA 2020 guidelines. Data sources were obtained from the Scopus and Google Scholar databases, covering publications from 2017 to 2025. Of the total 714 articles identified, eight articles met the inclusion criteria and were analyzed thematically. The results of the study show that the application of AI in inclusive education requires mastery of three main dimensions of teacher competence, namely technical foundations, ethical awareness, and inclusive pedagogy. AI has the potential to strengthen personalized learning, foster equitable access, and improve the psychological well-being of students. However, teacher readiness, training limitations, and weak policy support remain major obstacles to its implementation. This study emphasizes the need to strengthen teachers' AI literacy through targeted professional training, education policies that support inclusivity, and ethical governance that is adaptive to technological dynamics. The results of this review are expected to form the basis for the development of policies and programs to improve teacher competence in the era of artificial intelligence.